Release of scars improve pain, vertebral mobility and reduce the degree of disability in chronic low back pain: Scar release and low back pain - Sakabe, Fabiana Forti; Alves Ferreira, Fernanda; Cagliari Rizzi, Gabriela Eduarda; Maronezi, Varley Augusto; Iwai Sakabe, Daniel; Bortolazzo, Gustavo Luiz (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Scars are the inevitable result of injuries, and visceral scar adhesions can generate local and referred pain, through viscerosomatic reflexes. Studies report the existence of relationships between scar adhesions in the abdominal region and low back pain (LBP). Objective: to evaluate the immediate and late effect of manual release techniques on abdominal scars on the intensity of LBP, spinal mobility and the degree of lumbar disability in individuals with chronic LBP. Methods: 18 volunteers of both genders (15 women and 3 men) with LBP and abdominal scars participated in the study. Pain intensity (VAS), spinal mobility (finger-floor test and lateral inclinations) and degree of lumbar disability (Oswestry questionnaire) were measured. After the assessments, scar release treatment was carried out using manual techniques (gliding, rolling, fascial techniques) for 15 minutes. Immediately after the session, the reassessment (VAS and mobility) was carried out. Two more sessions were carried out with an interval of one week between them and seven days after the 3rd session the final reassessment will be carried out, using the visual analogue scale, oswestry questionnaires and spinal mobility, similarly to the initial assessment. Results: The intensity of LBP was significantly reduced after the sessions, remaining lower seven days after the intervention. There was an improvement in spinal mobility, measured by finger-to-floor tests and lateral inclinations after scar release. The volunteers also had a reduction in the degree of lumbar disability after the intervention, demonstrating a reduction in the impact of LBP on carrying out activities of daily living. Conclusion: The protocol with 3 sessions of manual scar release proposed presented an immediate and late effect, significantly reducing the intensity of LBP, promoted improvement in spinal mobility and reduced the degree of lumbar disability in the volunteers studied. It is worth noting that these effects remained seven days after completion of treatment.